2022
DOI: 10.1167/tvst.11.2.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physiological Oxygen on Primary Human Corneal Endothelial Cell Cultures

Abstract: Purpose Primary human corneal endothelial cells (HCEnCs) cultured in room air are exposed to significantly higher O 2 concentrations [O 2 ] than what is normally present in the eye. We evaluated the growth and metabolism of HCEnCs cultured under physiological [O 2 ] (2.5%; [O 2 ] 2.5 ) and room air ([O 2 ] A ). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
0
10
1
Order By: Relevance
“…Western blots were performed similarly to published protocols [22]. Protein was isolated from confluent PC3 and MCF7 cultures.…”
Section: Western Blotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blots were performed similarly to published protocols [22]. Protein was isolated from confluent PC3 and MCF7 cultures.…”
Section: Western Blotsmentioning
confidence: 99%
“…For half of the wells, the incubation in minimal medium included addition of 10 nM E2 and the other half served as control without E2. The Seahorse XFe24 sensor cartridges and drugs were prepared according to manufacturer protocols as previously described by our laboratory [22]. The assay medium was Seahorse XF Dulbecco's modified Eagle medium, with 1.2 mM glutamine, 7.0 mM glucose, and 0.45 mM pyruvate.…”
Section: Seahorse Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that evaluating cancer cells under physioxia could more closely recapitulate their physiopathologic status in the in vivo microenvironment. Although IEO studies are generally performed at 18-21% oxygen, several have examined the benefits of growing other ex vivo models in physioxia ( 34 37 ). For example, kidney organoids cultured in physiological hypoxia (7% oxygen) instead of 21% oxygen showed enhanced sprouting and interconnectivity while maintaining renal cell types and their spatial organization ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, kidney organoids cultured in physiological hypoxia (7% oxygen) instead of 21% oxygen showed enhanced sprouting and interconnectivity while maintaining renal cell types and their spatial organization ( 33 ). Primary human corneal endothelial cells can successfully be cultured at 2.5% oxygen resembling in vivo corneal aqueous environment containing 2.8% oxygen ( 37 ). Compared to room air (∼21% oxygen), corneal endothelial cells cultured at physiological hypoxia showed considerable differences in cell metabolism, viability, oxygen-consuming reactions, and glycolytic metabolism.…”
Section: Introductionmentioning
confidence: 99%